An Analysis of the use of Accounting and Market Measures of Performance in Executive Compensation Contracts - Lambert, Richard A.; Larcker, David F. (Journal of Accounting Research, 1987)
Richard A. Lambert, David F. Larcker, An Analysis of the use of Accounting and Market Measures of Performance in Executive Compensation Contracts, Journal of Accounting Research, Vol. 25, Studies on Stewardship Uses of Accounting Information (1987), pp. 85-125